2004
DOI: 10.1177/1534735404268054
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Transformative Process: Experiences of Cancer Patients Receiving Integrative Care

Abstract: Purpose. The purpose of this study is to describe the essential features of the transformative experience among people living with cancer who are seeking integrative care and to identify factors supporting this process. It is hoped that after establishing the nature and meaning of this change or shift, one will better understand what is most meaningful in terms of providing appropriate care and support to patients seeking integrative care. Study Design. An interpretational, qualitative approach guided sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 16 publications
3
57
0
1
Order By: Relevance
“…A longer term study could utilise a rolling series of MYCaW questionnaires to demonstrate changes in concerns and valued effects over time. Such studies may also throw more light onto the changes found by in-depth qualitative work, such as 'transformation' [26] and 'unstuckness' [31] which have not been elucidated in our work to date.…”
Section: Discussionmentioning
confidence: 99%
“…A longer term study could utilise a rolling series of MYCaW questionnaires to demonstrate changes in concerns and valued effects over time. Such studies may also throw more light onto the changes found by in-depth qualitative work, such as 'transformation' [26] and 'unstuckness' [31] which have not been elucidated in our work to date.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the general population found that CAM users are more likely to report having had a transformational experience that changed how they saw the world. 16 Integrative medicine, defined as the integration of CAM and conventional medicine, can provide patients with a context in which transformation can occur 39 ; cancer as well can provide this context. Survivors find comfort in CAM's emphasis on the spiritual aspects of well-being.…”
Section: Commentmentioning
confidence: 99%
“…16,[21][22][23][24][25] Yet, only 2 studies that focus on the outcomes associated with 2 IM practice models have been reported in the literature. Mulkins and Verhoef 26 described the healing experiences of 11 patients with cancer who received care in 3 different IM practices characterized as multidisciplinary. They stated that patients "became more aware of who they are and how they relate to the world" and described how patients moved through an evolutionary, transformative process of change that produced a shift in well-being and a changed worldview.…”
mentioning
confidence: 99%